Tandem Mass Spectrometry Screening for Inborn Errors of Metabolism in Newborns and High-Risk Infants in Southern China: Disease Spectrum and Genetic Characteristics in a Chinese Population - Tan, Jianqiang; Chen, Dayu; Chang, Rongni; Pan, Lizhen; Yang, Jinling; Yuan, Dejian; Huang, Lihua; Yan, Tizhen; Ning, Haiping; Wei, Jiangyan; Cai, Ren (Frontiers in Genetics, 2021)
Inborn errors of metabolism (IEMs) lack specific clinical manifestations, often causing progressive and irreversible neurological damage, physical and intellectual development lag or even death, and serious harm to the family and society. The screening of neonatal IEMs by tandem mass spectrometry (MS/MS) is an effective method for early diagnosis and presymptomatic treatment to prevent severe permanent sequelae and death. Dozens of genetic metabolic diseases, such as amino acid metabolic disorders, organic acid metabolic disorders, and fatty acid oxidation disorders, can be screened for simultaneously with high flux and high accuracy by determining the amino acid and acylcarnitine content in neonatal dried blood on filter paper. This method has gradually become popular in China in recent years. Significant differences in IEMs spectra, prevalence, and genetic characteristics exist among the different regions and populations in China. A total of 111,986 healthy newborns and 7461 hospitalized high-risk infants were screened for IEMs using MS/MS to understand the characteristics of IEMs and related gene mutations in newborns and high-risk infants in Liuzhou. Positive samples were analyzed by Sanger sequencing or next-generation sequencing. The results showed that the incidence of IEMs in newborns in the Liuzhou area was 1/3733, and the incidence of IEMs in high-risk infants was 1/393. Primary carnitine deficiency (1/9332), phenylketonuria (1/18,664), and isovaleric acidemia (1/37,329) ranked the highest in neonates, while citrullinemia type Ⅱ ranked the highest in high-risk infants (1/1865). Further, 56 mutations of 17 IEMs-related genes were found in 49 diagnosed children. Among these, HPD gene c.941T>C, CBS gene c.1465C>T, ACADS gene c.337G>A, c.1195C>T, ETFA gene c.737G>T, MMACHC gene 1076bp deletion, PCCB gene c.132-134delGACinsAT, IVD gene c.548C >T, c.757A>G, GCDH gene c.1060G>T, and HMGCL gene c.501C>G were all unreported variants. Some related hotspot mutations were found, including SLC22A5 gene c.51C>G, PAH gene c.1223G>A, IVD gene c.1208A>G, ACADS gene c.625G>A, and GCDH gene c.532G>A. These results show that the overall incidence of IEMs in the Liuzhou area is high. Hence, the scope of IEMs screening and publicity and education should be expanded for a clear diagnosis in the early stage of the disease.